Scientific Research of the BookKeeping Account, which Had Been Carried Out at the Vilnius University (the Years 1965-2004) - Mackevičius, Jonas (Ekonomika, 2005)
Urgency of the topic. The bookkeeping account within the conditions of the world’s competitive market becomes a serious economic problem, which should be constantly investigated. The book·keeping account provides various information, which is used for investigations control management and forecasting of the company’s and its subdivi.ions’ activity. The more influence is produced by the competitors and by the other external forces upon the company, the more important possession of the qualitative account system, which would enable to calculate the income and expenditures correctly, to provide an operative and objective information so as to take various decisions, is. It can be stated that the well-managed bookkeeping account ensures the company’s profitable activity and is the factor of each company’s development and prosperity. However, how should the bookkeeping account be managed? Which registers and documents are to be used? How should the account information be accumulated and kept? How and for which purposes should it be used? A lot of such and similar questions can be asked and no correct answer will be given. if no scientific research is carried out.The object of the investigation: the scientific research of the bookkeeping account, which had been carried out by the Account and Audit Chair of the Vilnius University for the years 1965-2004.The goal of the investigation: ascertainment of the most important results of the scientific research of the bookkeeping account, obtained by the lecturers of the Account and Audit Chair, and formulation of the directions of the further investigation.The methods and sources of the investigation: the scientific analysis of the works, issued by the lecturers and those, who are working for the doctor’s degree; the methods of comparison, grouping, detailing and summarizing of the information. In the course of the investigation, mostly the material of the publication “Bibliography of the Scientific Publications, Issued by the Lecturers of the Faculty of the Economic Cybernetics and Finances” (the year 1981 and the year 1986; creator J.Laskovas) and File I 12, kept in the archive of the Account and Audit Chair of the Faculty of Economics “The Plans and Reports of the Annual Scientific Research Work” were used.The scientific research of the bookkeeping account is of great importance, seeking to assure protection of the company’s assets, consumption of the national resources, transparency of all economic operations and deals, efficient application of the financial information so as to take the decisions on management.Lecturers of the Vilnius University and of the Lithuanian Agricultural University and those, who are working for the doctor’s degree, as well as representatives of several other institutions have carried out and are carrying out the scientific research of the Lithuanian bookkeeping account system. The article reveals the topics of the scientific research, which was carried out by the Account and Audit Chair of the Vilnius University within the years 1965-2004, the results of the investigation and the most important publications.The investigation has proved that within the soviet period the lecturers of the Account and Audit Chair of the Vilnius University and those, who are working for the doctor’s degree, had been successfully carrying out the scientific research in the field of account of the production costs and calculation of the products’ prime-cost. Peculiarities of accounting of the production costs and of calculation of the products’ primecost at the companies, attributed to the machine, lathe, device, textile, sewing, furniture, knitted wear and meat producing industry and construction, at the trade and agricultural companies and organizations were investigated; 16 theses for the doctor’s degree were defended; more than 100 scientific articles and several books of monographic character were published.After having restored independence of Lithuania, the investigation of rearrangement of the system of the bookkeeping account according to the requirements of the market economics, has been started on a larger scale (not only of account of the production costs and calculation of the products’ prime-cost). It was revealed in the course of the investigation that a lot of mistakes were done while creating the system of the bookkeeping account within the period of independent Lithuania, i.e. the laws on the bookkeeping account and the other documents, regulating management of accounting, were not timely approved; the institutions of the methodological direction and supervision of accounting were not created; the conception of rearrangement of the Lithuanian bookkeeping account and of its further improvement were not prepared, etc.Seeking for the faster integration of the Lithuanian bookkeeping account into the European Union’s account system, it is suggested to establish the department of the scientific research of the bookkeeping account problems at the Account Institute of the Republic of Lithuania. Its main function would be to analyze the account condition in Lithuania’s economy and to submit the proposals on practical application of the progressive forms of account and its methods.